ANALYSIS OF FACTORS AFFECTING THE FORMATION OF TAX DEBT AND TAX COLLECTIONS IN THE SUBJECTS OF THE NORTH CAUCASIAN FEDERAL DISTRICT - Igor Yu. Pelevin (Статистика и экономика, 2016)
The article is devoted to estimation of factors, which impact on formation of the tax debt in the regions. Description of the dynamics of the tax debt in the North Caucasus Federal District from 2009 to 2011 is given. Also an analysis of this tax debt was made according to the subjects of the federal district. Proposals to form an active fiscal policy are formulated based on this analysis.